2018
DOI: 10.1055/s-0038-1636904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orbicularis Muscle Resection during Blepharoplasty on the Position of the Eyebrow

Abstract: Dermatochalasis is a skin excess in the upper eyelid which may be associated with either an aesthetic and functional defect, blocking the peripheral vision. Upper blepharoplasty is the gold standard procedure for correction of dermatochalasis and to restore youthful contours to the periorbita. It is one of the most commonly performed procedures in aesthetic plastic surgery; however, there is still a lack of consensus about this procedure. The excess skin is sometimes removed alone or in conjunction with a stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…They found that the brow tends to move upward or remain at the same level one year after the upper eyelid blepharoplasty with the excision of 5 mm of the orbicularis oculi strip. [12] They thought the opposition of forces between the elevator and the eyebrow depressors was liable for their result. After the 5 mm orbicularis strip resection cause weakened the depressor mission of the orbicular muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the brow tends to move upward or remain at the same level one year after the upper eyelid blepharoplasty with the excision of 5 mm of the orbicularis oculi strip. [12] They thought the opposition of forces between the elevator and the eyebrow depressors was liable for their result. After the 5 mm orbicularis strip resection cause weakened the depressor mission of the orbicular muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that muscle should be resected as much as skin, while others recommend resectioning a part approximately 2 mm that will expose only the septum. [11,12,13]. Authors who argue for the preservation of orbicular muscle during surgery emphasize that muscle is important for improving esthetic outcomes and maintaining a youthful appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from affecting its appearance, this also makes the eyelid deformed, forming triangular eyes. In severe cases, the pupil is blocked, and the eyelid function is affected, causing the patient’s visual field in the lateral upper quadrant to be impaired 13–15 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [1][2][3][4][5][6][7][8][9][10] have reported on the position of the upper eyelids or eyebrows before and several months after upper blepha-roplasty or ptosis surgery, but currently no studies have reported on the eyelid position during or immediately after surgery. To our knowledge, there are currently no reports that have focused on the lower eyelid position in upper eyelid surgery.…”
mentioning
confidence: 99%